The Result Of A Study Of The Current Situation In The Consumer Market In The Production Of Special Clothing - Sheralieva Risolat Islamjon daughter; Tashpulatov Salikh Shukurovich (Genius Publishing Group, 2022)
This article describes the anylysis of examples of the world’s special clothing production industry
Keywords: special clothing; DuPont; Ansell Edmont